Preservation of Language Processing and Auditory Performance in Patients With Disorders of Consciousness: A Multimodal Assessment - Ferraro, Stefania; Nigri, Anna; D'Incerti, Ludovico; Rosazza, Cristina; Sattin, Davide; Rossi Sebastiano, Davide; Visani, Elisa; Duran, Dunja; Marotta, Giorgio; Demichelis, Greta; Catricala', Eleonora; Kotz, Sonja; et al. (Frontiers in Neurology, 2020)
The impact of language impairment on the clinical assessment of patients suffering from disorders of consciousness (DOC) is unknown or underestimated, and may mask the presence of conscious behavior. In a group of DOC patients (n=11; time post-injury range:5-252 months), we investigated the main neural functional and structural underpinnings of linguistic processing, and their relationship with the behavioral measures of the auditory function, using the Coma Recovery Scale-Revised (CRS-R). We assessed the integrity of the brainstem auditory pathways, of the left superior temporal gyrus and arcuate fasciculus, the neural activity elicited by passive listening of an auditory language task and the mean hemispheric glucose metabolism. Our results support the hypothesis of a relationship between the level of preservation of the investigated structures/functions and the CRS-R auditory subscale scores. Moreover, our findings indicate that patients in minimally conscious state minus (MCS-): 1) when presenting the auditory startle (at the CRS-R auditory subscale) might be aphasic in the receptive domain, being severely impaired in the core language structures/functions; 2) when presenting the localization to sound might retain language processing, being almost intact or intact in the core language structures/functions. Despite the small group of investigated patients, our findings provide a grounding of the clinical measures of the CRS-R auditory subscale in the integrity of the underlying auditory structures/functions. Future studies are needed to confirm our results that might have important consequences for the clinical practice.